Local peoples’ knowledge and perceptions of Australian wattle (Acacia) species invasion, ecosystem services and disservices in grassland landscapes, South Africa - Thozamile S. Yapi; Charlie M. Shackleton; David C. Le Maitre; Luthando E. Dziba (Ecosystems and People, 2023)
ABSTRACTMany alien tree species were introduced into grassland ecosystems in South Africa by the commercial forestry industry for paper and timber for furniture. Over decades some of these introduced species escaped into neighbouring farms and community land. Adult trees from these alien species now provide other ecosystem services, notably fuelwood. Depending on the spatio-temporal context, many of these species can also negatively affect ecosystem services. We collected interview data from commercial and communal farmers in the upper Umzimvubu catchment in South Africa to compare farmers’ knowledge and perceptions of invasive wattle species invasion and their associated ecosystem services and disservices. Fuelwood and fencing poles were the most common uses of wattle by commercial (83%; 67%) and communal (99%; 49%) farmers. On the other hand, the reduction of grass cover and loss of grazing land were the most commonly mentioned negative impacts of wattles by commercial (83%; 75%) and communal (92%; 80%) farmers. Although both groups recognise the importance of wattles in providing ecosystem services, most communal farmers perceived wattles to have more negative effects than benefits. The findings demonstrate that both farmer groups highly depend on ecosystem services and are affected by disservices of wattles. However, while large-scale commercial households favour the presence of wattles in the landscape, communal households prefer complete removal of the wattles from the landscape. This may be due to lack of locally available alternative options or inability to replace or purchase ecosystem services affected by wattles from other sources or markets like commercial farmers.